A sustainability education academic development framework (SEAD). Issue 8 (16th November 2016) - Holdsworth, Sarah; Thomas, Ian
Abstract : Academic development is one means of reorientating education within higher education (HE) to include sustainability principles. This paper identifies the requirements of academic development programmes that will provide educators with the skills to engage students in the ideas of sustainability and sustainable development. In order to determine what an ideal academic development programme for sustainability education might look like, a theoretical framework for sustainable education and academic development (SEAD framework) was constructed. This was based on an analysis of the literature in the areas of sustainability education, academic development and organisational change in HE. The aim of this paper was to present and analyse the theoretical SEAD framework against three international academic development programmes in sustainability education for HE, which utilised different approaches and delivery modes. From this analysis, it is possible to determine the elements of academic development that would most likely result in a change in educational development and delivery.